The Effectiveness of Natural Science Handouts Based on Critical Thinking Skills on the Diversity of Living Things - Ramayanti Panjaitan; Dharmono Dharmono; Suyidno Suyidno (Universitas Muhammadiyah Sidoarjo, 2022)
The development of critical thinking skills is one of the key factors to face the opportunities and challenges of life in the industrial era 4.0. However, this skill has not been trained properly. Therefore, the purpose of writing this paper is to analyze the effectiveness of science handouts on the material diversity of living things to improve students' critical thinking skills. This study uses formative evaluation with Tessmer Model, which is limited to small group and field tests. The trial used a one group pretest and posttest design, for a small group test on 12 students and a field test on 20 class VIII students of SMPN 1 Sungai Durian. Collecting data through critical thinking tests and interviews. The results of the research on the small group and field tests showed: (1) students' skills in interpretation, analysis, explanation, evaluation, and inference were initially low to moderate; and (2) students' critical thinking skills increased significantly at = 5%, with n-gain in the moderate criteria. Thus, the science handout based on critical thinking skills that was developed is effectively used in science learning.